Improving water properties to increase infiltration characteristics - Soppe, Richard W. O., author; Styles, Stuart W., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
Water properties, such as the viscosity and surface tension, can be affected by temperature and surfactants to increase infiltration rates into soils. Specifically, they will change the hydraulic conductivity of the soil. A simple soap solution and the new material PAM (inexpensive polymer chemical) were evaluated as surfactants. Laboratory experiments and field tests on a site in Davis, California were done to quantify the effects of changing the water properties. Additional effects, like the improved soil structure during infiltration and less soil particles in tailwater (reduced erosion due to runoff) were observed and are described in this paper. The conclusions of this study are translated into suggestions for improved on-farm water use in furrows, sprinklers, and drip irrigation.
USCID 14th technical conference
Not digitized by CSUL Digital Services.
Presented at Contemporary challenges for irrigation and drainage: proceedings from the USCID 14th technical conference on irrigation, drainage and flood control held on June 3-6, 1998 in Phoenix, Arizona.